A study on factors that would affect employee turnover at Encorp Berhad / Nashua Ishar - Ishar, Nashua (Faculty of Business and Management, 2011)
High rate of employee turnover is continues to be a serious problem for businesses in many organizations world-wide. High employee turnover in the construction and properties industry is unavoidable aspect. Encorp Berhad is not excluded for the above matters. This model theorizes a linear or straight-line relationship between the dependent variables which is job turnover and the independent variables which are job satisfaction, organizational commitment and employee commitment. Therefore, this study is a conceptualized to determine the nature and degree of the relationship between these independent variables with job turnover.